Transient modeling of plunger lift with check valve for gas well deliquification in horizontal well. Issue 1 (31st December 2023) - Jia, Youliang; Shi, Shuqiang; Tian, Wei; Tan, Bo; Yang, Yacong; Li, Xuri
ABSTRACT: To improve the plunger gas lift efficiency, a modified plunger was developed by adding a check valve to the downhole positioner in the Changqing Gas Field. However, the transient flow behavior of the plunger lift with check valve is unclear owing to the lack of a reliable method. Therefore, in this study, a simplified transient mechanistic model based on the law of conservation of momentum and mass is proposed to simulate the comprehensive dynamic process of a plunger-lift system. The results of the proposed method exhibited a high coincidence with that of the accumulated gas and liquid production of gas Well-1 in one cycle, and the relative errors were 2.11% and 4.29%, respectively. The calculation results demonstrate that the plunger lift with check valve can effectively prevent the flow of liquid to the bottom of the well, reduce the bottom hole flow pressure, and increase the productivity of gas well during the shut-in period. The efficiency of the plunger lift with check valve was enhanced with an increase in the volume of the accumulated liquid unloaded from the bottom of gas wells. Additionally, for the plunger lift with check valve, the production peak value was higher and the instantaneous gas production peak value was lower in comparison with the conventional plunger. After the plunger reached the wellhead, the instantaneous fluid production of the conventional plunger was relatively unstable than that of the plunger lift with check valve. A certain distance should be maintained from the bottom of the well in the case of the positioner with check valve. If the positioner is placed at the bottom of the tubing, the difference between the lift efficiency of the plunger with check valve and conventional plunger is small, and lower than that of the conventional plunger. The installation position of the downhole positioner in a gas well should be below the accumulated liquids level and should maintain a certain distance between the positioner and bottom of the well (200 m). The results of this study enhance the understanding of the operation mechanism of the plunger lift with check valve, and unloading of the accumulated liquids from the bottom of gas wells.